2022
DOI: 10.1021/acscatal.2c02052
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed anti-Markovnikov Hydroalkylation of Trifluoromethylalkenes

Abstract: Transition-metal-catalyzed difunctionalization of olefins constitutes a fertile synthetic platform for rapid access to complex molecules from bulk chemicals. However, substrates featuring fluoroalkyl substituents are rarely employed because of facile β-fluoride elimination pathways. Herein, we report a hydroalkylation of trifluoromethylalkenes with alkyl halides under nickel catalysis that enables the rapid construction of 1,1,1-trifluoropropane derivatives. The common β-fluoride elimination pathway is suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 78 publications
0
25
1
Order By: Relevance
“…The recent studies also demonstrated reactions without β-fluoride elimination as TfOH-HFIP-mediated hydroarylation, nickel-catalyzed anti-Markovnikov hydroalkylation, and metal-catalyzed cycloaddition and hydroaddition reactions …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The recent studies also demonstrated reactions without β-fluoride elimination as TfOH-HFIP-mediated hydroarylation, nickel-catalyzed anti-Markovnikov hydroalkylation, and metal-catalyzed cycloaddition and hydroaddition reactions …”
Section: Introductionmentioning
confidence: 98%
“…A wide set of various reactions, including S N 1′-, S N 2′-types, ipso-substitutions, defluorinative functionalization, and so forth, is based on successful C−F bond activation with transition metals or photoredox catalysts to construct more complex fluorinated substrates. 16 The recent studies also demonstrated reactions without βfluoride elimination as TfOH-HFIP-mediated hydroarylation, 17 nickel-catalyzed anti-Markovnikov hydroalkylation, 18 and metal-catalyzed cycloaddition and hydroaddition reactions. 19 At the same time, CF 3 derivatives of styrenes are target molecules in various fields of science and technology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 In 2022, Feng and co-workers reported a Ni-catalyzed anti-Markovnikov hydroalkylation of trifluoromethylalkenes. 13 On the contrary, recently functionalization of α-(trifluoromethyl)-styrenes without accompanying defluorination could be achieved on the basis of nucleophilic addition. 14 Considering the importance of the 1,2-bis(trifluoromethylated) compounds in organic synthesis, we envisage that construction of these chemicals by utilizing α-(trifluoromethyl)alkenes as readily available synthons without defluorination of the trifluoromethyl group is worth exploring.…”
mentioning
confidence: 99%
“…In 2021, a photoredox-catalyzed hydroalkylation of DNA-conjugated α-(trifluoromethyl)­styrene was achieved by Molander . In 2022, Feng and co-workers reported a Ni-catalyzed anti-Markovnikov hydroalkylation of trifluoromethylalkenes . On the contrary, recently functionalization of α-(trifluoromethyl)­styrenes without accompanying defluorination could be achieved on the basis of nucleophilic addition .…”
mentioning
confidence: 99%
“…However, almost all reported procedures involve the defluorination process from an α-CF 3 alkylmetal intermediate via β-F elimination, thus giving the corresponding gem-difluoroalkenes as main products (path a) . The CF 3 -compatible catalytic functionalization through the electrophilic trapping of the intermediate is theoretically possible but still remains underdeveloped (path b), except for specially designed substrates conjugated with additional activating groups such as vinyl, Ar, NO 2 , and carbonyl …”
mentioning
confidence: 99%